2021
DOI: 10.3390/mi12020184
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Microparticle Transport and Deposition Mechanics in Rhythmically Expanding Alveolar Chip

Abstract: : The transport and deposition of micro/nanoparticles in the lungs under respiration has an important impact on human health. Here, we presented a real-scale alveolar chip with movable alveolar walls based on the microfluidics to experimentally study particle transport in human lung alveoli under rhythmical respiratory. A new method of mixing particles in aqueous solution, instead of air, was proposed for visualization of particle transport in the alveoli. Our novel design can track the particle trajectories u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…There were two kinds of experimental platform because of the different ways of placing the alveolar chip. When the alveolar chip was placed horizontally, the high-speed camera was mounted on the microscope (IX73, Olympus, Tokyo, Japan), as shown in Figure 1 C. When the chip was placed vertically, the high-speed camera was fixed on a small anti-vibration platform, and the chip was fixed on the displacement platform ( Figure 1 D), which was similar to the previous published work [ 31 ]. Image-pro plus 6.0 was used for particle tracking in image post-processing.…”
Section: Methodssupporting
confidence: 74%
See 4 more Smart Citations
“…There were two kinds of experimental platform because of the different ways of placing the alveolar chip. When the alveolar chip was placed horizontally, the high-speed camera was mounted on the microscope (IX73, Olympus, Tokyo, Japan), as shown in Figure 1 C. When the chip was placed vertically, the high-speed camera was fixed on a small anti-vibration platform, and the chip was fixed on the displacement platform ( Figure 1 D), which was similar to the previous published work [ 31 ]. Image-pro plus 6.0 was used for particle tracking in image post-processing.…”
Section: Methodssupporting
confidence: 74%
“…However, we also observed that most particles directly settled to the bottom of the alveolus at the last several generations from the 21st generation. We could also find some hints of the irreversibility and gravity effect on the particle transport and deposition from the studies performed by Fishler et al [ 22 ] and Dong et al [ 31 ], showing the trajectory within a limited number of cycles.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations